Developing educational goals: insights from a Peer Assisted Teaching Scheme. Issue 4 (1st October 2016) - Ross, Bella; Carbone, Angela; Lindsay, Katherine; Drew, Steve; Phelan, Liam; Cottman, Caroline; Stoney, Sue
Abstract: The rapid changes facing higher education are placing increased focus on the quality of the student experience, achieving learning outcomes, and employability expectations. As a result, academics in teaching roles are increasingly measured on performance via student evaluations amplifying attention on professional development initiatives for academics. One such initiative is the Peer Assisted Teaching Scheme currently in practice across many Australian universities. The critical component of the scheme is the establishment of teaching goals that provide focus and direction for the peer partnership. This study addresses two questions: (1) Around which aspects do academics set their goals for teaching improvement? and (2) How do academics' goals align with the SMART goal-setting framework that is prescribed in the scheme? Findings from five Australian universities showed that goals align with a variety of educational areas yet many were underdeveloped, or misaligned with the proposed strategy. The implications of this are discussed and a framework for setting education goals for teaching improvement is developed.